Češko-slovaški literarni odnosi v 30. in 40. letih 19. stoletja - Zelenková, Anna (Primerjalna književnost, 2015)
The paper explores the growing interest of Czech literary circles in the Slovak cultural scene during the 1830s and 1840s. It was then that this attention was reflected in the increasing quantity of Slovak publications in Czech periodicals and in the more frequent occurrence of Slovak themes in the works of Czech authors. Standing for more than an interesting, "exotic" theme, "Slovakness" became part of the Czech concept of literary mutuality and its endeavor to pursue a cultural and language alliance within the tribal unity. Among the Slovak themes introduced to the Czech context, special appeal was held by the character of the tinker, often perceived as a particular type of Slovak patriot with Romantic attributes.
Keywords: Tyl, Josef Kajetán, 1808-1856; Chmelenský, Josef Krasoslav, 1800-1839; Czech literature; češka književnost; Slovak literature; slovaška književnost; 19. st.; literarni odnosi; češko-slovaški literarni stiki